Dose Analysis of BNCT Treatment Method for Rhabdomyosarcoma in the Head and Neck Regions Based on PHITS Code - Dhani Nur Indra Syamputra; Yohannes Sardjono; Rida Siti Nur’aini Mahmudah (Universitas Gadjah Mada, 2018)
The objectives of this research were to ?nd (1) the optimum boron dose for treating rhab- domyosarcoma in the head and neck regions and (2) the effective irradiation time to treat rhab- domyosarcoma in the head and neck regions. This research used the particle and heavy ions transport code system (PHITS) to simulate the neutron source and BNCT doses. The neutron source used was Kartini Reactor. The simulation was carried out by creating the geometry of cancer tissue in the head and neck regions. Boron concentration variance was 30, 35, 40, 45, and 50 µg/g tissue. The output of PHITS was a neutron ?ux and neutron dose. The neutron ?ux value was used to acquire the alpha dose, proton dose, and gamma dose inside the tissue. The results showed that (1) the optimum boron dose for treating rhabdomyosarcoma in the head and neck regions was 50 µg/g tissue and (2) the effective irradiation time was 7 hours and 4 minutes, which was acquired with a boron concentration of 50 µg/g tissue. The higher the boron concentration level, the higher the dose rate, the quicker the irradiation time, and the lower the radiation dose received by healthy tissues.